2012
DOI: 10.1111/j.1349-7006.2012.02248.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive activity of CD14+ HLADR cells in squamous cell carcinoma of the head and neck

Abstract: Myeloid‐derived suppressor cells (MDSC) represent a heterogeneous population and have the potential to suppress immune responses via diverse mechanisms. In recent studies, a new subset of MDSC was identified by the markers CD14+ and HLA‐DR− in the peripheral blood from cancer patients. In this study, we investigated the proportions and characteristics of CD14+ HLA‐DR− cells in patients with squamous cell carcinoma of the head and neck (SCCHN). As expected, the percentage of CD14+ HLA‐DR− cells was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 29 publications
(66 reference statements)
2
83
0
Order By: Relevance
“…Therefore, it may be of interest to investigate whether the serum concentration of CXCL10 or CCL2 is a useful prognostic marker for patients with cancer. A higher frequency of CD14 + HLA-DR low / -monocytes in RCC patients was observed compared with healthy donors, confirming observations made in previous studies (8)(9)(10) , cells with a lower HLA-DR expression or are negative for HLA-DR; COX2, cyclooxygenase 2; TGF-β, transforming growth factor β; IL, interleukin; CCL2, chemokine (C-C motif) ligand 2; CXCL10, chemokine (C-X-C motif) ligand 10; OSM, oncostatin M; VEGF, vascular endothelial growth factor; RCC, renal cell carcinoma.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, it may be of interest to investigate whether the serum concentration of CXCL10 or CCL2 is a useful prognostic marker for patients with cancer. A higher frequency of CD14 + HLA-DR low / -monocytes in RCC patients was observed compared with healthy donors, confirming observations made in previous studies (8)(9)(10) , cells with a lower HLA-DR expression or are negative for HLA-DR; COX2, cyclooxygenase 2; TGF-β, transforming growth factor β; IL, interleukin; CCL2, chemokine (C-C motif) ligand 2; CXCL10, chemokine (C-X-C motif) ligand 10; OSM, oncostatin M; VEGF, vascular endothelial growth factor; RCC, renal cell carcinoma.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have revealed that cancer patients exhibit an increase in the number of cluster of differentiation (CD)14 + human leukocyte antigen (HLA)-DR low / -cells, those with a lower HLA-DR expression or are negative for HLA-DR, circulating in the blood (8)(9)(10). CD14 + HLA-DR low / -cells that were isolated from cancer patients were identified to suppress T-cell activation in culture, and thus these CD14 + HLA-DR low / -monocyte populations were considered to act as MDSCs (6,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…MDSCs are a heterogeneous population of cells composed of precursors of macrophages, granulocytes, dendritic cells, and myeloid cells at earlier stages of differentiation (5). These cells have been demonstrated to have the potential to suppress immune responses of T cells by way of TGFb, Arg1, programmed death ligand (PD-L) 1, and reactive oxygen species (ROS), as well as by regulatory T cell induction (6)(7)(8)(9)(10)(11). In mice, MDSCs are characterized by the coexpression of Gr-1 and CD11b.…”
Section: H Epatitis B Virus (Hbv) Infection Is a Major Global Healthmentioning
confidence: 99%
“…Treatment with PD-1 dramatically increases the T-cell population and IFN-γ production in head and neck cancer patients, in whom PD-1 positive myeloid-derived suppressor cells were detected in peripheral blood [16].…”
Section: Pd-1/pd-l1 In Oral Cancers and Hpv Infectionsmentioning
confidence: 99%
“…However, virus-like particle (the major HPV virion protein L1)-based two prophylactic vaccines: quadrivalent Gardasil (HPV16/18/6/11) and bivalent Cervix (HPV16/18) are available. In 2014, the US FDA has approved a nonavalent vaccine against nine HPV types ( HPV6,11,16,18, 31, 33, 45, 52 and 58) but these vaccines are not commercialized well in developing countries [4][5][6]. …”
mentioning
confidence: 99%